2014
DOI: 10.12991/mpj.2014187238
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and larvicidal and adult topical activity of some hydrazidehydrazone derivatives against Aedes aegypti

Abstract: A series of novel hydrazide-hydrazone derivatives were synthesized and evaluated for their larvicidal and adult topical activity against Aedes aegypti. The proposed structures of all the synthesized compounds were confirmed using elemental analysis, UV, IR, 1 H-NMR, 13 C-NMR and mass spectroscopy. Compounds 4a-h were screened in larval bioassays at concentrations of 100, 50 and 25 ppm in a dose dependent manner and data for their mortality was recorded. Among the tested compounds, 1-(4-nitrophenyl)-3-(4-{2-oxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Direct topical application to adult females produces an LD 50 , a quantitative measure, for a strain; the method has been used for extensive screening of natural products as well as laboratory derived compounds (Pridgeon et al 2008). Permethrin adult topical assays and larval assays were conducted following protocols described previously (Akdag et al 2014;Chang et al 2014). The same technical grade permethrin was used to make a dilution series to provide an independent measure for comparison to the results observed in the CDC bottle bioassays.…”
Section: Toxicological Assaysmentioning
confidence: 99%
“…Direct topical application to adult females produces an LD 50 , a quantitative measure, for a strain; the method has been used for extensive screening of natural products as well as laboratory derived compounds (Pridgeon et al 2008). Permethrin adult topical assays and larval assays were conducted following protocols described previously (Akdag et al 2014;Chang et al 2014). The same technical grade permethrin was used to make a dilution series to provide an independent measure for comparison to the results observed in the CDC bottle bioassays.…”
Section: Toxicological Assaysmentioning
confidence: 99%
“…Permethrin adult topical assays and larval assays were conducted following protocols described previously (Akdag et al 2014;Chang et al 2014). The same technical grade permethrin was used to make a dilution series to provide an independent measure for comparison to the results observed in the CDC bottle bioassays.…”
Section: Toxicological Assaysmentioning
confidence: 99%
“…25 The synthesized dipyrromethane N-acyl hydrazone derivatives exhibited moderate to extremely strong cytotoxic effects against HL-60 (leukemia) and HCT-116 (colon) cancer cells according to a different study by Gautam et al 26 Novel (R,S)-etodolac derivatives containing the N-acyl hydrazone moiety synthesized by Koçet al have been found to have good cytotoxic effects against PC-3, DU-145, and LNCaP cell lines (prostate cancer). 27 Further, N-acyl hydrazones are well-known to exhibit a wide spectrum of biological properties as antioxidant, 28−31 analgesic, 32 anti-inflammatory, 33−35 antimicrobial, 36−41 antiviral, 42,43 anticonvulsant, 44 antiprotozoal, 45 antimalarial, 46 larvicidal, 47 antituberculosis, 48 and antifungal 49 activity. Some compounds with known biological activities containing the N-acyl hydrazone structure are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Further, N -acyl hydrazones are well-known to exhibit a wide spectrum of biological properties as antioxidant, analgesic, anti-inflammatory, antimicrobial, antiviral, , anticonvulsant, antiprotozoal, antimalarial, larvicidal, antituberculosis, and antifungal activity. Some compounds with known biological activities containing the N -acyl hydrazone structure are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%